Budaya Hukum Yang Hidup Dalam Masyarakat Indonesia Ditinjau Berdasarkan KUHP Nasional Nomor 1 Tahun 2023 - Andi Wulan Rahmadania; Muhammad Rizcky Afriyandi; Masayu Nilam Permata Sari; Elsi Kartika Sari (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Legal culture is a reflection of the mindset, attitudes, and behavior of society towards applicable legal regulations, playing an important role in the formation of legal awareness. In Indonesia, legal culture is formed from a combination of customary values, religion, and the influence of the colonial legal system. Amendments to the Criminal Code (KUHP) through Law Number 1 of 2023 replace the old Criminal Code left behind by the Dutch which is considered no longer relevant, by adjusting criminal regulations to the values ​​of modern society and paying attention to customary law as "living law." The new Criminal Code introduces various controversial provisions related to insulting the government, freedom of expression, and the implementation of the death penalty, which have triggered various responses from society and influenced the existing legal culture. This study uses a descriptive qualitative method with a literature study approach to identify the influence of changes to the Criminal Code on legal culture in society. The results show that the integration of customary law in the Criminal Code strengthens local cultural values ​​and a sense of justice, but faces challenges related to its implementation in accordance with the principles of legality and human rights. The role of local governments in issuing relevant regulations is important so that customary law can be implemented effectively. The integration of customary law into the Criminal Code is expected to enrich the Indonesian legal system in accordance with social developments, as well as support the development of a more inclusive legal culture that reflects the characteristics of Indonesian society